Hubungan Antara Kekerasan Psikologis Guru Dengan Self-Esteem dan Tingkat Stres Siswa SMK “X” Kabupaten Bandung (Jurnal Bimbingan dan Konseling Islam, 2015)
Psychological violence has characteristics disguise himself and sometimes becomes an ideology which justified as protection measures for the benefit of students. Nevertheless, violence in any form contrary to the educational foundation, so this study aims to identify the relationship of psychological violence that teachers do with self-esteem and stress levels of vocational studentsl. The method used is correlational research. The research sample of 146 students of class XI of SMK majoring in Software Engineering "X" Bandung regency suffered psychological violence from subject teachers Programming nonprobability Desktop by using sampling techniques. The research data obtained through the instruments developed by the researchers. The results showed that: (1) there is a relationship between psychological violence teacher with self-esteem of vocational students SMK "X" with the Bandung District rxy1 = 0.460; (2) there is a relationship between psychological violence with the level stress student teacher of SMK "X" with the Bandung District rxy2 = 0.565. Recommendations, this study aimed to educators who teach in both formal and non-formal schools.